Scoring of Deformed Costal Cartilages Reduces Postoperative Pain after Nuss Procedure for Pectus Excavatum - Nagasao, Tomohisa; Hamamoto, Yusuke; Tamai, Motoki; Kogure, Tetsukuni; Jiang, Hua; Takano, Naoki; Tanaka, Yoshio (The Thoracic and Cardiovascular Surgeon, 2016)
Objective The present study aims to elucidate whether or not scoring deformed cartilages reduces postoperative pain after the Nuss procedure for pectus excavatum patients.Methods A total of 46 pectus excavatum patients for whom the Nuss procedure was conducted were included in the study. The patients were categorized into two groups, depending on whether or not the supplementary maneuver of scoring deformed cartilages was performed in addition to the Nuss procedure. Patients for whom deformed costal cartilages were scored were categorized as the Scoring Group (n = 24); those who received no such scoring were categorized as the Non-Scoring Group (n = 22). After evaluating the maximum stresses occurring on the thoraces by means of dynamic simulation using finite element analyses, intergroup comparison of the maximum von-Mises stress values was performed. Furthermore, after quantifying postoperative pain as the frequency with which patients injected anesthetics through an epidural pain-control system within 2 postoperative days, the degree of pain was compared between the two groups.Results The maximum stresses occurring on the thorax were significantly greater for the Non-Scoring Group than for the Scoring Group; injection frequency was also greater for the Non-Scoring Group (average 4.9 times for 2 days) than for the Scoring Group (average 2.5 times for 2 days).Conclusion High stresses occur due to the performance of the Nuss procedure, causing postoperative pain. The stresses can be reduced by performing supplementary scoring on deformed cartilages. Accordingly, postoperative pain is reduced.
Keywords: chest; treatment; anesthesia